Residu b_4,6(n) terhadap modulo 2 dan 3 - Fadhlan Zhaahiran; Uha Isnaini (UNIVERSITAS NEGERI PADANG, 2023)
Integer partition is a branch of number theory that is still developing today. A partition of a positive integer n is a way to express as a sum of positive integers without counting the order. Let denote the number of partitions of . We discover arithmetic properties of which is the number of partitions of an integer n where the parts are not multiple by 4 or 6.